Artificial supercavitation - Lau, Daniel Guan Rong (2018)
Supercavitation has been utilized in the past, specifically in military technology as a measure implemented to reduce the skin drag of bodies traversing through a liquid medium. The technology has been successfully implemented and has garnered significant amount of success. In the case of the military, underwater projectiles – such as torpedoes – have reached speeds greatly surpassing that of its normal counterparts. Such is the case of the Russian torpedo in 1977, VA-111 Shkval, which can travel at speeds exceeding 100 metres per second. Another example would be the SPP-1 Underwater Pistol, which was developed by the Soviet Union for use in 1971. The barrel of the gun is not rifled, and the bullet’s trajectory is dependent on hydrodynamics and in this case, the supercavity is what provides the stability of the projectile motion. The collapse of which, causes the fired projectile to grow unstable and veer off course. A more recent example would be the marine craft known as “Ghost”. Ghost is a high-speed marine vehicle developed by Juliet Marine System and is widely considered a fully functioning supercavitating vessel. The water-based vehicle is partially submerged during operation and boasts speeds of up to 57 miles an hour in the water. This new vehicle is well known for its stability and smooth riding conditions – making it a potential avenue for further civilian applications. [29] There has also been effort put into developing supercavitation to enhance transportation underwater. More recently in 2014, China announced plans to place emphasis on research to develop an underwater submarine for high speed travel underwater. Potentially, the phenomena of supercavitation would allow speeds of up to approximately 1482 metres per second. However, physical results have yet to be seen regarding this application, but should it prove to be possible, it would be possible to travel from Shanghai to San Francisco in as fast as 100 minutes. Due to the high velocity nature of the technology, most of the interest in the technology are for military applications. As in the case of the research performed by the Chinese, the technology is also beneficial towards transport applications. One consideration in which case however, would be the elevated velocities and the measures that would have to be put in place such that the passengers can withstand the resulting G forces. Until such measures are realizable, it is perhaps more realistic to consider the implementation of the technology in freight or cargo applications. This report serves as a compiled review of literature comprising the findings of previous work with regards to studies conducted to understand the supercavitation process and its various aspects. The author hopes that the review serves as an effective reference for subsequently proposed methodologies. Crucial areas for future research are also highlighted towards the end of the report.